NAVIGATING OBSTACLES IN WRITING SCHOLARLY ARTICLES FOR REPUTABLE INTERNATIONAL JOURNAL PUBLICATION - Lafu Salu, Martinus; Emilia, Emi; Gin Gustine, Gin (University of Kuningan, 2025)
The following are the issues raised by this study: 1) What are the challenges that English lecturers face when writing research articles for scholarly publication in a reputable international journal? 2) What are the most significant impediments that English lecturers face when writing research articles for scholarly publication in a reputable international journal. The dominance of English in global studies has recently become an issue of debate in the publishing sector. Writing academic papers in English has grown more significant. However, faculty members and postgraduate students face writing barriers in a number of areas, including knowledge claim, textual organization, interference from diverse cultural perspectives, linking the text to the audience, argument structure, grammatical rules, and so on. According to the findings of this study, one of the most common difficulties that researchers encounter while writing is selecting how to claim expertise. Furthermore, they emphasize the importance of writing and publishing in a well-known international indexed journal for the benefit of themselves, their university, and their country. They argue that the university should offer them a course, training, or workshop.